DAYA TERIMA COOKIES SUBSTITUSI TEPUNG AMPAS TAHU DENGAN TEPUNG BERAS MERAH DAN NILAI GIZINYA - Riris Manurung; Ernawati Nasution; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Tofu dregs flour with brown rice flour can be processed into a variety of food products one of them cookies that can contribute nutrients such as protein, fat, carbohydrates and fiber for the fourth nutrient content is an important component that is necessary for every human being. The purpose of this study was to determine the acceptability and nutrition facts of tofu dregs flour with brown rice flour as the main ingredient in the manufacture of cookies. This study was an experimental study of making cookies with the addition of tofu dregs flour with brown rice flour with different ratio of tofu dregs flour with brown rice flour (70% : 30% and 80% : 20%). Research on testing the acceptability and manufacture of cookies substitution held at the Faculty of Public Health, University of Sumatera Utara with panelists were 30 people, while nutrient analysis was tested in Laboratory of Industrial Research and Standarization Agency Medan. This type of research is an experiment using a completely randomized design. The data were analyzed descriptively percentage. Results of research organoleptic test on taste, scent, texture and colour of the cookies substituted with tofu dregs flour with brown rice flour at a ratio of 70% : 30% protein contributed 12.51%, 13.72% fat, carbohydrates 69.0% and 11.20% crude fiber in 100 grams of material. While the ratio of 80% : 20% protein contribute as much as 13.17%, 13.50% fat, carbohydrates 68.42% and 12.13% crude fiber in 100 grams of material. From the results of test Independent Sample Test can be seen a difference in the treatment that there is no difference in treatment effect on the flavor (0.325) ,scent (0.143) and colour (0.581) between cookies with a ratio of 70 % : 30 % and a ratio of 80 % : 20 %. While on the texture (0,004) between cookies ratio of 70 % : 30 % and a ratio of 80 % : 20 % there is a difference in treatment effect. Suggestions from this study is that people can make cookies tofu dregs flour with brown rice flour as a healthy snack alternative, inexpensive and can reduce waste pollution tofu waste. In addition, further research needs to be done related to the content of other nutrients in the cookies tofu Dregs Flour with brown rice flour. Keywords : Cookies, Tofu Dregs Flour, Brown Rice Flour.